PENGARUH PEMBERIAN TEPUNG LIMBAH KULIT ROTI TAWAR TERHADAP PERSENTASE BOBOT ORGAN DALAM PADA ITIK MOJOSARI JANTAN (Anas platyrhynchos) - Lutvia Nur Fasa; Achmad Jaelani; Irwan Zakir; Raga Samudera; Sugiarti Sugiarti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
This study aims to study the effect of giving bread waste on the percentage of weight viscera in Male Mojosari Ducks (Anas platyrhynchos). Two-week-old male Mojosari ducks were obtained from the Livestock Breeding Center for Animal Feed forage with 100 animals, the feed used was composed of fine bran, concentrate, fish meal, bread flour, coconut oil, vitamins, and minerals.  Metod used a Completely Randomized Design.  The used 5 treatments 4 replications consisting of 10% TR0 Bread Flour + 90% feed ration, TR20 20% Bread Flour + 80% feed ration, TR30 Bread Flour 30% + 70% feed Ration, and TR40 Bread Flour 40% + 60% Ration feed. The variables measured were heart weight percentage, heart weight percentage, and gizzard weight percentage.  Research data were analyzed using Homogeneity Test and Variance Analysis Test. The results of this study indicate that the provision of bread waste flour in a ratio of no less than 40% can increase the percentage of heart weight and does not affect the liver and gizzard.